Enhanced C3H6/C3H8 separation performance in polysulfone membrane blended with rigid ZIF-8 crystals - Luo, Jiayu; Lyu, Luxi; Yin, Zongjie; Wei, Yanying (Frontiers of chemical science and engineering, 2025)
Metal-organic frameworks have a wide range of applications in the field of membrane separation, but the inherent flexible structure and the difficulty for scale-up hinder their further applications. Herein, the relatively rigid zeolitic imidazolate framework-8 particles prepared under an electric field (E-ZIF-8) were used as the fillers in polysulfone (PSF) to form series of mixed matrix membranes. It was found that the introduction of E-ZIF-8 improves both the C 3 H 6 permeability and C 3 H 6 /C 3 H 8 selectivity of the membranes. Compared with the bare PSF membrane, the C 3 H 6 /C 3 H 8 selectivity of the 30 wt % E-ZIF-8@PSF membrane increased by ∼230%, while the C 3 H 6 permeability was enhanced by ∼830%. In addition, time and pressure dependence analysis demonstrated that such E-ZIF-8@PSF membranes also exhibited good long-term stability and pressure resistance, offering significant industrialization advantages.